STRATEGI PERSONAL BRANDING WALIKOTA SURABAYA CAK ARMUJI PADA AKUN TIKTOK @cakj1 - Fitriawardhani, Tira; Muhammad Fadeli; Joanna Adelaida Prigelia Salindeho (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2025)
Some tiktok users use these applications creatively to remind themselves of society. As does in his tyres mayor Surabaya city @cakj1, he is flushing himself through the content he gives him. The research aims to endear content in tiktok @cakj1 to determine strategy personal branding an armuji on Surabaya citizens. In the study, the author employed the qualitative method of analyzing content with Peter montoya 2002's theory approach explaining that there are eight personal branding concepts, spesilization, leadership, differences, visibility, unity, and firmness a good name, through the content observation uploaded in ticktock @cakj1 and previous research and used the documentary study of screeenshoot social media content @cakj1 as a supplement to the study. The contents is